Overheating reduction in lightweight framed buildings with application of phase change materials - Zavrl, Eva (Strojniški vestnik, 2020)
The trend of lightweight framed building structures is gaining in popularity. Due to lower accumulation capability and thermal stability, buildings might be inclined to higher risk of overheating. The purpose of this study is to investigate overheating in lightweight framed buildings from the aspect of thermal comfort and energy efficiency in cooling season. Single-family house was modelled using DesignBuilder and located in moderate climate (Ljubljana, Slovenia). Heavyweight structure was compared to lightweight structure coupled with all 14 variations of phase change materials (PCM). Different strategies of PCM encapsulation (microencapsulated plasterboards, macroencapsulated additional layer), melting points (23 °C, 24 °C, 25 °C, 26 °C, 27 °C), capacities (M182, M91 M51, M27) and thicknesses (125 mm, 250 mm) of PCM were investigated and compared. The best passive solution was primarily evaluated based on the thermal comfort characteristics: average zone operative temperature (To) bends in cooling season. Secondarily, the additional energy needed for cooling within each solution was compared to the maximum allowed annual energy consumed for cooling specified in legislation. Consequently, the most influential parameter was the melting point of the PCM structure. Based on the chosen criteria, the overheating was significantly reduced using macroencapsulated layer with melting point of 24 °C and minimum capacity of M51 (max. To 26.3 °C). Heavyweight structure enabled lower To (27.1 °C) in the building compared to microencapsulated plasterboard solution with melting point at 23°C and thickness of 250 mm (28.8 °C). Correctly designed passive solution can be used for the improvement of the design strategy and legislation towards overheating prevention.
Keywords: energy efficiency; fazno spremenljive snovi; lahka gradnja; lightweight framed buildings; overheating; phase change materials; pregrevanje; raba energije; thermal comfort; toplotno ugodje